Consolidation of Academic Identity in the Nursing Profession - Balderas Gutiérrez, Karime Elizabeth (2024)
The change from technical training in Nursing to a scientifically based education influenced the process of configuration of academic identity in this profession. In this sense, the objective of this paper is to find the elements that characterize the academic identity of the nurse. For this purpose, the biographical method is used. The analysis of the information is carried out using the computerized qualitative analysis program Atlas.ti (2023). The results show that the consolidation of the academic identity in Nursing is a product of the research practice from the epistemological perspective of care, the application of knowledge based on nurse thinking and evidence-based Nursing, without leaving aside the historical, educational and labor processes that make up its professional subculture. This study contributes to the study of the professions from the educational field, revealing the micro-social processes that occur in the different professions.